PRODUKSI DAN PENDAFTARAN PIRT PRODUK LOKAL DESA WISATA TISTA SEBAGAI STANDARISASI PEMASARAN PRODUK - Putra, A.M.; Ariana, I.N.J.; Sulistyawati, A.S.; Sutaguna, I.N.T. (Buletin Udayana Mengabdi; Vol 24 No 1 (2025): Buletin Udayana Mengabdi, 2024)
Tista Tourism Village, which is an agricultural area, has great potential in developing entrepreneurship or developing community through home industry to produce food and beverage products whose raw materials are very abundant. The raw materials available are abundant and the processing process is not too complicated, resulting in people turning to the food and beverage industry. With an area of around 52.00 ha in Tista Village, it has the potential to be linked to the development of local culinary products in Tista Tourism Village with production continuity and PIRT registration as standardization of marketing of Tista Tourism Village products. This activity aims to motivate and mobilize the community to utilize community agricultural, plantation, livestock and fishery products through post-harvest processing into various attractive, creative and innovative finished products, and is supported by legality registration and product standardization through the PIRT Registration which is recognition and legality regarding the suitability of the product produced and guaranteeing the health of the product so that it can be consumed healthily and safely.Observation patterns with schemes for strengthening community participation, namely: community participation models, increasing entrepreneurial capacity, and technology transfers. The benefits received by the Tista Village community in service activities resulted in various types of local food from the Tista Tourism Village and the issuance of a Home Industry Food Product Certificate for Radesta Coffee Products. Keywords : PIRT Registration, Local Product, Products Standardization, Product Marketing, Tourism Village